Endometriomas: the effectiveness of combination treatment - Natalia V. Artymuk; Olga A. Zotova; Ekaterina N. Vaulina (IP Berlin A.V., 2021)
Aim. Evaluate the effectiveness of combined treatment and establish the frequency of recurrence of the ovarian endometrioma. Materials and methods. The prospective observational study evaluating the effectiveness of combined treatment of endometriomas, established the frequency of relapse after treatment. 186 patients with an established diagnosis of endometriosis of the ovaries were monitored, who underwent operative treatment in the volume of laparoscopic cystectomy. 95.0% of patients received anti-relapse hormonal treatment. Results. Against the background of treatment, positive dynamics were noted: dyspareunia, hyperspolymenorrhea and pre- and postmenstrual bloody discharge were stopped in 98.7% of cases, dysmenorrhea in 97.4% of cases, chronic pelvic pain in 94.8% cases. Pregnancy occurred in 11.7% of cases (1.3% of which when using assisted reproduction). The recurrence rate of endometriomas after 2 years was 1.4%, after 3 years 3.7%. Conclusion. Combination treatment was effective in reducing the severity or completely cured the symptoms of endometrioid ovarian cysts in 95% of women. The recurrence rate of endometriomas after 2 years was 1.4%, after 3 years 3.7%.